PENGARUH METODE PRAKTIKUM TERHADAP HASIL BELAJAR FISIKA SISWA PADA MATERI ALAT POKOK OPTIK - Sijabat, Apriani; Simamora, Benny Leonardo; Sianipar, Herna Febrianty; Roulina, Christa Voni; Sidabutar, Ropinus (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The objective of this study is to investigate the effect of practicum method on student learning outcomes in the subject matter of optical tools in grade XI semester II SMA Swasta Asisi T.P. 2022/2023 with the application of practicum method.The type of research is true experiment with the sample from grade XI MIA 1 and XI MIA 2 of SMA Swasta Asisi T.P. 2022/2023. The instrument test of research was composed 20 items of multiple choice and the validity of the content was tested by two experts as the validator and the observation sheet of the student activity. Based on the result of the data analysis, the mean value of post test in  experimental class postes 78.46 with the standard deviation of 11.25 and the mean value of post test in control class 66.50 with the standard deviation of 13.78. Normality and homogeneity test at level α=0.05 stated normal and homogeneous and test of hypothesis was only one thitung > ttabel (2.99 > 1.67). It can be concluded that the using of  practicum method can improve the student’s achievement in the subject of optical tools in grade XI semester II SMA Swasta Asisi T.P. 2022/2023.